2008
DOI: 10.1002/jsfa.3170
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and nutritional evaluation of Jatropha protein isolate prepared by steam injection heating for reduction of toxic and antinutritional factors

Abstract: BACKGROUND: Jatropha kernel contains 400-600 g oil kg −1 , and the cake obtained after oil extraction is rich in protein. The use of Jatropha cake/meal in food or feed is limited owing to the presence of toxic and antinutritional constituents. The main objective of the present study was to prepare protein isolates with reduced toxic and antinutritional factors and improved nutritional quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 32 publications
9
50
1
1
Order By: Relevance
“…The protein content of RPI was similar to canola protein isolate (Mwachireya et al, 1999), but more than those reported by for rapeseed protein isolate (Nagel et al, 2012), pea protein isolate (Schulz et al, 2007), canola protein isolate (Slawski et al, 2013) and jatropha protein isolate . Isolating the proteins from rubber kernel meal resulted in a significant increase in the protein content and reduction in the antinutritional factors as reported by other researchers in different studies (Devappa and Swamylingappa 2008;Saetae and Suntornsuk, 2010;Nagel et al, 2012;Kumar et al, 2012;Slawski et al, 2013). The higher in vitro digestibility of RPI recorded in this study may be due to the significant reduction in the soluble and indigestible carbohydrates, antinutritional factors, and more accessibility of amino acid peptide bonds by the digestive enzymes as reported by Devappa and Swamylingappa (2008).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The protein content of RPI was similar to canola protein isolate (Mwachireya et al, 1999), but more than those reported by for rapeseed protein isolate (Nagel et al, 2012), pea protein isolate (Schulz et al, 2007), canola protein isolate (Slawski et al, 2013) and jatropha protein isolate . Isolating the proteins from rubber kernel meal resulted in a significant increase in the protein content and reduction in the antinutritional factors as reported by other researchers in different studies (Devappa and Swamylingappa 2008;Saetae and Suntornsuk, 2010;Nagel et al, 2012;Kumar et al, 2012;Slawski et al, 2013). The higher in vitro digestibility of RPI recorded in this study may be due to the significant reduction in the soluble and indigestible carbohydrates, antinutritional factors, and more accessibility of amino acid peptide bonds by the digestive enzymes as reported by Devappa and Swamylingappa (2008).…”
Section: Discussionsupporting
confidence: 80%
“…Isolation of protein is one of such approach by separating the pure protein fractions from other non-proteinaceous components present in the ingredients including antinutritional factors (Mwachireya et al, 1999;Devappa and Swamylingappa, 2008;Saetae and Suntornsuk, 2010;Wanasundara, 2011), thus improve the digestibility and nutrient utilization. In the present study, the protein content of the isolated protein (RPI) from rubber kernel meal was found to be 908 g kg −1 with a concomittant reduction in the cyanide contents (64.3%), phytic acid (51.1%), tannin (92.4%) and insoluble carbohydrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein digestibility-corrected amino acid score (PDCAAS) PDCAAS was calculated according to the method of Sarwar and McDonough (1990) using the essential amino acid composition of the test samples and amino acid patterns suggested by FAO/WHO/UNU for 10-12 year old children and adults (Devappa and Bhagya 2008).…”
Section: Mineral Estimationmentioning
confidence: 99%
“…Tannins and several other toxins and antinutritional factors, e.g. phorbol esters, phytate, and glucosinolate, can also be degraded or removed under alkaline conditions [96][97][98].…”
Section: Leavesmentioning
confidence: 99%